Enhancement of photocatalytic hydrogen evolution activity of porous oxygen doped g-C3N4 with nitrogen defects induced by changing electron transition - Jiang, Yabin (2020)
Porous structure, nitrogen defects and oxygen dopants are simultaneously introduced into the framework of graphitic carbon nitride (g-C3N4) by a simple co-pyrolysis of dicyandiamide and ammonium persulphate ((NH4)2S2O8). The (NH4)2S2O8 plays multi-function roles in the co-pyrolysis process. It not only restrains polycondensation to generate nitrogen defects but also introduces porous structure and oxygen dopants due to its strong oxidative ability. The synergetic effect of the nitrogen defects and oxygen dopants leads to the change of π band state and LP state (lone pair electrons), causing the change of electron transition in the modified g-C3N4. The transitions from impurity levels play a predominant role in excitation process while the transition from intrinsic HOMO to LUMO becomes subordinate, which improve the charge separation significantly. The modified g-C3N4 exhibits excellent photocatalytic hydrogen evolution activity under visible light illumination, which is almost 6 times higher than pristine g-C3N4 because of the improved efficiency of charge separation and increased specific surface area. These findings provide a simple and efficient method to improve the photocatalytic activity of g-C3N4 by changing the electron transition through a rational band structure engineering.